Experimental evidence of strong relationships between soil microbial communities and plant germination. (17th April 2021) - Eldridge, David J.; Travers, Samantha K.; Val, James; Ding, Jingyi; Wang, Jun‐Tao; Singh, Brajesh K.; Delgado‐Baquerizo, Manuel
Abstract: Plant‐associated microbes play essential roles in nutrient uptake and plant productivity, but their role in driving plant germination, a critical stage in the plant life cycle, is still poorly understood. We used data from a large‐scale, field‐based soil seed bank study to examine the relationship among plants germinating from the seed bank and soil microbial community composition. We combined this with an experiment using 34 laboratory‐based microcosms whereby sterile soil was inoculated with microbes from different field sites to examine how microbes affect the germination of nine plant species. The community composition of plants in the soil seed bank was highly and significantly associated with bacterial and fungal community composition, with stronger correlations for soil beneath plant canopies. Microbes predicted a unique portion of the variation in the community composition of germinants after accounting for differences in environmental variables. The strongest correlations among microbes and plant functional traits included those related to perenniality, growth form, plant size, root type and seed shape. Our microcosm study showed that different plant species had their own associated germination microbiome, and most plant–microbe interactions were positive during germination. Synthesis . Our study provides evidence for intimate relationships between plant and soil biodiversity during germination. Our work fills an important knowledge gap for plant–microbe interactions and reveals valuable insights into the shared natural history of plants and microbes in terrestrial ecosystems. Abstract : Intimate relationships exist between plants and microbes during the germination process. Different plant species had their own associated germination microbiome, and most plant–microbe interactions were positive during germination. These microbial interactions illustrate the shared natural history of plants and microbes in terrestrial ecosystems.